The Supernatant of Tonsil-Derived Mesenchymal Stem Cell Has Antiallergic Effects in Allergic Rhinitis Mouse Model - In-Su Park; Ji Hye Kim; Jun-Sang Bae; Dong-Kyu Kim; Ji-Hun Mo (Hindawi Limited, 2020)
Background and Purpose. Recently, tonsil-derived mesenchymal stem cells (T-MSCs) have attracted great attention in various medical fields due to easier harvest of T-MSCs and more immunomodulatory effects than adipose-derived MSCs. However, there was still little evidence of the effect of conditioned media from T-MSCs (T-MSCs-CM) on allergic rhinitis (AR). Therefore, we investigated the impact of T-MSCs-CM on an AR mouse model. Methods. We isolated T-MSCs from human palatine tonsil and evaluated the ingredients of T-MSCs-CM. The effect of T-MSCs-CM was evaluated in the AR mouse model that was randomly divided into five groups (negative control, positive control, and T-MSCs-CM treated (0.1 mg, 1 mg, and 10 mg)). To investigate the therapeutic effect, we analyzed rhinitis symptoms, serum immunoglobulin (Ig), inflammatory cells, and cytokine expression. We also assessed T cell receptor signal, including MAP kinase (ERK/JNK), p65, and NFAT1. Results. We identified the increment of TGF-β1, PGE2, and HGF in the T-MSCs-CM. In an animal study, the T-MSCs-CM-treated group showed significantly reduced allergic symptoms and infiltration of eosinophils and neutrophils in the nasal mucosa, whereas there was no significant difference in total IgE and the OVA-specific IgE level. Additionally, we found that the 10 mg T-MSCs-CM-treated group showed a significantly decreased IL-4 mRNA expression, compared to the (+) Con group. In the analysis of T cell receptor signal, the phosphorylation of MAP kinases, translocation of p65, and activation of NFAT1 were inhibited after T-MSCs-CM. Conclusions. Our findings suggest that T-MSCs-CM showed a partial immunomodulatory effect on the AR mouse model by the inhibition of T cell activation via MAP kinase, p65, and NFAT1.